Indicators of AEI Applied to the Delaware Estuary - Lawrence W. Barnthouse; Douglas G. Heimbuch; Vaughn C. Anthony; Ray W. Hilborn; Ransom A. Myers (The Scientific World Journal)
We evaluated the impacts of entrainment and impingement at the Salem Generating Station on fish populations and communities in the Delaware Estuary. In the absence of an agreed-upon regulatory definition of “adverse environmental impact” (AEI), we developed three independent benchmarks of AEI based on observed or predicted changes that could threaten the sustainability of a population or the integrity of a community.